Effects of different stabilizers on the quality of calamansi concentrate - Golez, Sharyn Gumabon
Four lots of calamnsi concentrate samples were prepared using three different stabilizers : Gum Tragacanth (lot GT), Gellan Gum (lot GG), Xanthan Gum (lot XG) and a control lot with no added stabilizer.